O processo histórico do Ensino De Ciências no Brasil: concepções e perspectivas formativas no contexto do Ensino Fundamental - Santos, Daiane Rodrigues da Costa (Brasil, 2023)
The present study seeks to investigate the Active Methodologies applied to Science Teaching, in the contexto of the initial grades of Elementary School. The debate is articulated with the following problematization: how does the learning process in Science occur in the initial grades of Elementary School and what is the contribution of Active Methodologies to favor this learning? Based on this, the presente work aimed to carry out a bibliographical survey on the Active Methodologies of Science Teaching and its implication in the initial grades of Elementary School. Therefore, to meet the following specific objectives: a) To analyze the historical trajectory of Science teaching in Brazil; b) Systematize and understand the process of Active Methodologies applied in Science in the context of the initial grades of Elementary Education. The study demonstrated in its historical analysis that political and social aspects influenced the didactic conceptions of Science Teaching. In this contexto, the teaching of Science constitutes a privileged space in which the diferente explanations about the world, the phenomena of nature and the transformation produced by man can be exposed and compared. Therefore, this knowledge needs to be socially constructed and historically accumulated, in addition to a close relationship whit social and technological issues.